Efektivitas Media Sosial dalam Pemasaran Digital Rumah Sakit: Literature Review - Yohana Septiani Merrynda; Helen Andriani (Syntax Corporation, 2023)
The development of technology is currently developing rapidly. This also has an impact on the health sector. Every hospital is required to be able to make innovations, especially in marketing in the digital era. Social media is a powerful instrument in the current millennial era and since 2021 there are 4.66 billion internet users in the world or 59.5% of the population and social media users totaling 4.20 billion or 53.6% of the population. According to We Are Social, it states that the use of social media in Southeast Asia is ranked 6th and is 69% of internet users per country, indicating that internet user data in Indonesia since 2021 is 202.6 million people or 73.3% of the total population. Indonesia's population is 274.9 million people. The purpose is to review the effectiveness of social media in digital marketing in hospitals. The method uses a literature review approach from the